ASSESSMENT ON DIMENSIONS OF AUTHENTIC LEADERSHIP OF COLLEGE TEACHERS - Arceño, Rose A; Ag, Saiffullah Idris M; Adamu, Tanimu Ibrahim (PEOPLE: International Journal of Social Sciences, 2019)
This study described a theory-based measure of authentic leadership using three separate samples obtained from Indonesia, Ar-Raniry State Islamic University; Nigeria, Bayero University; and the Philippines, Palompon Institute of Technology. A multidimensional model of the authentic leadership construct (the Authentic Leadership Questionnaire [ALQ]) comprising leader self-awareness, relational transparency, internalized moral perspective, and balanced processing was used in gathering the data from the identified school samples. Finally, the results revealed a high level of self-awareness, internalized moral perspective, balanced processing, and relational transparency from the three samples. This implies that the teacher-respondents as professionals possessed stronger authentic leadership while performing their duties and responsibilities in the classroom. Conclusively, the pattern of leader behavior displayed promotes both positive psychological capacities and a positive ethical climate, fostering positive self-development. The classroom teachers are genuine, mission-driven and focused on results, lead with their heart, not just their minds, and focused on the long-term goals.